Pengaruh Good Corporate Governance, Ukuran Perusahaan, dan Pengungkapan Corporate Social Responsibility terhadap Nilai Perusahaan - Nabila Nabila; Eni Wuryani (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2021)
This study aims to prove and determine the effect of good corporate governance, company size and corporate social responsibility disclosure on firm value. The proxy for firm value is price to book value (PBV). The indicators used in GCG include managerial ownership, independent board of commissioners, and audit committee. Company size uses a proxy for total assets, while CSR disclosure is measured by the CSR index based on indicators from GRI (Global Reporting Initiatives) version G4. This study used property and real estate companies listed on the IDX in 2017-2019. The method used in this research is a quantitative method with a total of 22 companies. This study used multiple linear regression analysis techniques. The results simultaneously showed that Good Corporate Governance, Company Size, and Disclosure of Corporate Social Responsibility have an effect on firm value. Furthermore, the partial test results showed that GCG with the indicators of independent commisioner had a significant positive effect, the audit committee had a significant negative effect, firm size is proven to have an effect on firm value, while managerial ownership and CSR were not proven to have an effect on firm value.